Student-to-Student Cooperation in Virtual Learning without Breakout Rooms - Made Hery Santosa; Francisca Maria Ivone; George M Jacobs; Jenett C. Flores (Widya Mandala Surabaya Catholic University, 2022)
Education has increasingly turned to virtual learning in response to greater awareness of the benefits of virtual learning, increased technology to support learning outside of educational institutions, and, sadly, the advent of the COVID-19 pandemic. At the same time, awareness has also increased of the benefits of student-student cooperation, and technology to facilitate that cooperation has multiplied. Unfortunately, not all students have access to that technology. This article shares ideas, both low-tech and high-tech, to enhance the functioning of groups in virtual learning environments.